The Effect Of Compensation And Work Motivation On Employee Performance PT. Syamil Putra Jaya Tasikmalaya - Muhammad Luthfi Sani; Rita Tri Yusnita; Nita Fauziah Oktaviani (Universitas Dehasen Bengkulu, 2023)
This research aims to find out the simultaneous and partial effect between the compensation and work motivation on employee performance PT.Syamil Putra Jaya. The research method used is a quantitative method with a survey approach. The population in this research is the employee in PT.Syamil Putra Jaya which amounts is 118 people and the sample is 96 respondents who is an employee of the operational division used purposive sampling technique. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 25. The results showed that simultaneously the compensation and work motivation has significantly affect on employee performance. Partially the compensation has a significant effect on employee performance. Partially the work motivation has a significant effect on employee performance.